2022
DOI: 10.3390/ijms23063009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 6-Hydroxydopamine and Rotenone In Vitro Neurotoxicity on Differentiated SH-SY5Y Cells Using Applied Computational Statistics

Abstract: With the increase in life expectancy and consequent aging of the world’s population, the prevalence of many neurodegenerative diseases is increasing, without concomitant improvement in diagnostics and therapeutics. These diseases share neuropathological hallmarks, including mitochondrial dysfunction. In fact, as mitochondrial alterations appear prior to neuronal cell death at an early phase of a disease’s onset, the study and modulation of mitochondrial alterations have emerged as promising strategies to predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…No clear dose-dependent response was observed for any chemical, with the exception of the assay positive control, rotenone. Interestingly, significant mitochondrial texture modulation of HuWa TERT to rotenone (approximately 17.5%, Figure a) at 4 nM is 10 to 100 times lower than the in vitro mitochondrial morphology and function responses studies previously reported on different terrestrial mammals, such as human HepG2, SH-SY5Y, and rat cortical astrocytes cells. Comparable findings have also been reported on medical research council cell strain 5, developed from human fetal lung tissue …”
Section: Resultssupporting
confidence: 56%
“…No clear dose-dependent response was observed for any chemical, with the exception of the assay positive control, rotenone. Interestingly, significant mitochondrial texture modulation of HuWa TERT to rotenone (approximately 17.5%, Figure a) at 4 nM is 10 to 100 times lower than the in vitro mitochondrial morphology and function responses studies previously reported on different terrestrial mammals, such as human HepG2, SH-SY5Y, and rat cortical astrocytes cells. Comparable findings have also been reported on medical research council cell strain 5, developed from human fetal lung tissue …”
Section: Resultssupporting
confidence: 56%